2017
DOI: 10.1017/s0952523817000049
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical processing in vision

Abstract: Visual information reaches the cerebral cortex through a major thalamocortical pathway that connects the Lateral Geniculate Nucleus (LGN) of the thalamus with the primary visual area of the cortex (area V1). In humans, ~3.4 million afferents from the LGN are distributed within a V1 surface of ~2,400 mm2, an afferent number that is reduced by half in the macaque and by more than two orders of magnitude in the mouse. Thalamocortical afferents are sorted in visual cortex based on the spatial position of their rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 123 publications
(184 reference statements)
2
27
0
Order By: Relevance
“…Previous studies showed that orientation tuning in V1 is well predicted by the local arrangement of ON and OFF thalamic inputs (Jin et al, 2011;Lien and Scanziani, 2013), implying that functional circuits in V1 might initially be structured by thalamic afferents. In a subsequent study, Mazade and Alonso (2017) also suggested that observed variation of thalamo-cortical projection could play an important role in development of the cortical functions and in maximizing visual acuity. In addition, considering that neurons in the lateral geniculate nucleus (LGN) relay the receptive field of only one to three retinal ganglion cells (RGCs) in most cases (cat: Usrey et al [1999], monkey: Schein and de Monasterio [1987], mouse: Litvina and Chen [2017]), the structure of the LGN afferents reflects that of the retinal feedforward afferents.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies showed that orientation tuning in V1 is well predicted by the local arrangement of ON and OFF thalamic inputs (Jin et al, 2011;Lien and Scanziani, 2013), implying that functional circuits in V1 might initially be structured by thalamic afferents. In a subsequent study, Mazade and Alonso (2017) also suggested that observed variation of thalamo-cortical projection could play an important role in development of the cortical functions and in maximizing visual acuity. In addition, considering that neurons in the lateral geniculate nucleus (LGN) relay the receptive field of only one to three retinal ganglion cells (RGCs) in most cases (cat: Usrey et al [1999], monkey: Schein and de Monasterio [1987], mouse: Litvina and Chen [2017]), the structure of the LGN afferents reflects that of the retinal feedforward afferents.…”
Section: Introductionmentioning
confidence: 91%
“…It is also not clear how the geometrical realities imposed by different retinal designs might affect the arrangement of ON and OFF RGCs (see below for retinal designs). Mazade and Alonso (2017) propose that the spacing between thalamic axon patches with overlapping receptive fields needs to be greater than 2 axon patches to allow afferents to cluster within different cortical domains. As shown in Figure 4A, as the number of LGN neurons increases, the size of V1 increases in a non-linear fashion, as shown by the exponential plot (y = 770x 1.23 , R 2 = 0.98) (Stevens, 2001), i.e.…”
Section: Understanding Cortical Maps Through Understanding the Visualmentioning
confidence: 99%
“…The dotted vertical line shows the possible threshold between species with pinwheels and those without. Reproduced fromMazade and Alonso (2017) with permission from the copyright holder.…”
mentioning
confidence: 99%
“…When the model cortex size was large (gray squirrel 35,38 , 82 mm 2 ), introduction of LRCs increased both classification accuracy and small-worldness (Fig 4c, rightmost). In contrast, when the cortex size was small (mouse 35,39 , 3 mm 2 ), the performance and small-worldness did not increase further regardless of how many LRCs were added (Fig 4c, leftmost). In general, we found a strong correlation between the increment of performance (ΔPerf) and small-worldness (ΔSW) in relation to the variation of V1 size (Fig 4d).…”
Section: Resultsmentioning
confidence: 95%
“…All the other parameters (including input cell density, sparsity of feedforward connections, and V1 cell density) were assumed to be consistent across species. The anatomical data of averaged V1 size used in this study were from mouse 35,39 (3 mm 2 ), rat 35,54 (7 mm 2 ), tree shrew 50 (73 mm 2 ), and gray squirrel 35,38 (82 mm 2 ). Based on the tree shrew model (784 hidden units) we defined earlier, we set 900 units for gray squirrel, 25 units for the mouse and 64 units for the rat models.…”
Section: Methodsmentioning
confidence: 99%